GENETIC VARIATION OF SEED PHYSICO-CHEMICAL PROPERTIES OF GONGRONEMA LATIFOLIA ACCESSIONS IN RELATION TO THEIR SEEDLING PERFORMANCE - C. U. Agbo; S. C. Onyebara (Journal of Animal and Plant Sciences, 2013)
Genetic variation in physico-chemical properties of different accessions of Gongronema latifolia and contributions of such traits to seed emergence were investigated for two years in Nsukka. The study showed significant differences in the studied traits of the G. latifolia accessions. The accession, AC-05 had larger seeds as well as higher seed breadth and cotyledon thickness but lower level of abscisic acid (ABA) in both years. The seedling emergence capacity of the accessions in both years showed that the seedlings emerged earlier and more vigorous in the second year with reduced moisture content and ABA. Higher level of genotypic and phenotypic variance among the accessions on the measured traits occurred on the phenol content. Heritability estimates were higher in the chemical traits of the seeds than the physical traits with the exception of seed weight. Furthermore, the correlation coefficients suggest that accessions with larger seeds also have lower ABA and significantly higher vigorous emergence suggesting the impact of genetic factors in determining the performance of accessions. It was concluded that different accessions showed genetic differences in the seed traits which directly influenced emergence rate and vigour of seedlings over the two years.
Keywords: Genetic variation; seed traits; emergence; abscisic acid; Gongronema latifolia